ANALISIS PENGARUH CITRA PASAR TRADISIONAL TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI (Survei pada Konsumen Pasar Gede Solo) - Lamidi, Rina Wulandari, Rahayu Triastity & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
The purpose of the research are to analyses (1) the effect of the traditional market image to the consumer; (2) the effect of the traditional market image to consumer loyalty; (3) the effect of consumer satisfaction to consumer loyalty; (4) the effect of traditional market to consumer loyalty with cunsomer satisfaction as the mediating variable. Population on the research are the consumers of the Pasar Gede, Solo. There are 100 samples, taken with accidental sampling. Data colction technique use questionary through validity and reliability tests. Regression test requirements using classic assumption test. Data analysis technique using the line. The conslusion from the test result every hypothesis showing (1) the traditional market image have significant effect to the satisfaction of the consumer, therefore the 1st hypothesis is proven; (2) the traditional market image have significant effect to consumen of Pasar Gede Solo loyalty, therefore the 2nd hypothesis is proven; (3) The consumer satisfaction have significant effect to the Pasar Gede consumer, therefore hypothesis 3rd is proven; (4) The consumer satisfaction mediating traditional market image to Pasar Gede consumer loyalty, therefore the 4th hypothesis is proven.Keywords: traditional market image, consumer satisfaction, consumer loyalty